An Iron Uptake Operon Required for Proper Nodule Development in the Bradyrhizobium japonicum-Soybean Symbiosis - Heather P. Benson; Eric Boncompagni; Mary Lou Guerinot (Molecular Plant-Microbe Interactions, 2005)
Rhizobia live in the soil or enter into a nitrogen-fixing symbiosis with a suitable host plant. Each environment presents different challenges with respect to iron acquisition. The soybean symbiont Bradyrhizobium japonicum 61A152 can utilize a variety of siderophores (Fe[III]-specific ligands). Purification of iron-regulated outer membrane proteins had previously allowed the cloning of a gene, fegA, from B. ja-ponicum 61A152, whose predicted protein shares significant amino acid similarity with known TonB-dependent siderophore receptors. Here, we show that fegA is in an operon with a gene, fegB, that is predicted to encode an inner membrane protein. Characterization of fegAB and fegB mutants shows that both fegA and fegB are required for utilization of the siderophore ferrichrome. Whereas the fegB mutant forms a normal symbiosis, the fegAB mutant has a dramatic phenotype in planta. Six weeks after inoculation with a fegAB strain, soybean nodules do not contain leghemoglobin and do not fix nitrogen. Infected cells contain few symbiosomes and are filled with vesicles. As ferrichrome is a fungal siderophore not likely to be available in nodules, the symbiotic defect suggests that the fegAB operon is serving a different function in planta, possibly one involved in signaling between the two partners.